Pengaruh Core Stability Exercise terhadap Keseimbangan Pasien Stroke di Poli Rehabilitasi Medik RS Adhyaksa Jakarta: Case Study - Rokhim Sunandi; Ezra Bernadus Wijaya; Slamet Sumarno (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Stroke is a major cause of long-term disability and frequently results in balance impairment that limits functional mobility and increases the risk of falls. Impaired trunk control and postural instability are common consequences of stroke, highlighting the need for effective rehabilitation strategies. This study aimed to analyze the effect of Core Stability Exercise on balance improvement in stroke patients undergoing rehabilitation at the Medical Rehabilitation Polyclinic of RS Adhyaksa Jakarta. A case study design with a pretest–posttest approach was applied to three patients with ischemic stroke who presented with balance disorders. The intervention consisted of Core Stability Exercise, including bridging, bird-dog exercise, and seated balance exercise, conducted three times per week for eight sessions. Balance performance was measured using the Berg Balance Scale before and after the intervention. The findings demonstrated a consistent increase in Berg Balance Scale scores in all patients, indicating improvements in static and dynamic balance as well as a reduction in fall risk. Patients with better initial motor control showed faster and greater improvement, although positive changes were also observed in patients with more severe impairments. These results suggest that Core Stability Exercise contributes to enhanced trunk stability, postural control, and functional balance in stroke patients. The study implies that integrating Core Stability Exercise into routine physiotherapy programs may support more comprehensive and individualized stroke rehabilitation, particularly in addressing balance-related functional limitations.